PENGUKURAN EFISIENSI AGROINDUSTRI PANGAN LOKAL ENBAL DENGAN PENDEKATAN DATA ENVELOPMENT ANALYSIS - Natelda R Timisela; Ester D Leatemia; Febby J Polnaya; Rachel Breemer (JURNAL BUDIDAYA PERTANIAN, 2017)
The current research aimed to analyze the relative efficiency level of enbal (sago starch) agro-industries. The relative efficiency analysis on 32 DMUs of enbal agro-industries showed that 40,63% of the industries were efficient and 59.38% were inefficient. Every efficient DMU became the reference for the inefficient DMUs based on the suggested quality. Each DMU of the enbal agro-industries has not reached a good efficiency level, which was indicated by the average relative efficiency scale of 0.886. This was a relatively low value, and improvements on the use of production input were needed. The analysis result on the DMUs of the enbal agro-industries which were on constant return to scale position were 40,62%. This showed that enbal agro-industries actors have applied production input efficiently, for the production increase was equal to the use of input. In other words, the use of input was more proportional. The DMUs of enbal agro-industries which were on decreasing return to scale position were 15,63%. This showed that the use of production input had been unsuitable so that the output decreases and the production cost increased. Meanwhile, the DMUs that were on increasing return to scale position were 43,75%. This showed that the industry actors who used certain production input would create efficient DMUs. On the other hand, the input excess would possibly decrease the output. As a result, the industry actors should be concerned about the use of production input in order to establish business efficiency.